Percy Jackson and the battle of the labyrinth - Riordan,Rick (Puffin books: London, 2013)
"Honestly, blowing up another school was the last thing I wanted to do. As the son of a Greek God, I've had my share of near-death disaster - and now my arch enemy Luke wants to invade our camp via an ancient labyrinth. If he succeeds, thousands of bloodthirsty monsters will attack. So it's goodbye sunshine, hello darkness as four of us descend into the terrifying underground and beyond."
Keywords: English , Fiction